The Production of Swahili-Islamic Manuscripts with Specific Reference to Swahili Ink Making - Parkar, Ahmed (Islamic Africa, 2019)
This article briefly examines the production of Swahili-Islamic manuscripts with specific reference to Swahili ink making in coastal Kenya. The Swahili scribes used organic, carbonic and carbonic-iron inks to write their manuscripts for centuries. Currently, the knowledge on what sort of ink ingredients were used and how to make the inks themselves is in the domain of a dwindling number of elderly individuals. This paper tries to explain the types of ingredients mentioned by these individuals during interviews carried by the researcher in the period of 2015–2017 in East Africa.